First Description of the Karyotype and Sex Chromosomes in the Komodo Dragon (Varanus komodoensis) - Johnson Pokorná, Martina; Altmanová, Marie; Rovatsos, Michail; Velenský, Petr; Vodička, Roman; Rehák, Ivan; Kratochvíl, Lukáš (Cytogenetic and genome research, 2016)
The Komodo dragon (Varanus komodoensis) is the largest lizard in the world. Surprisingly, it has not yet been cytogenetically examined. Here, we present the very first description of its karyotype and sex chromosomes. The karyotype consists of 2n = 40 chromosomes, 16 macrochromosomes and 24 microchromosomes. Although the chromosome number is constant for all species of monitor lizards (family Varanidae) with the currently reported karyotype, variability in the morphology of the macrochromosomes has been previously documented within the group. We uncovered highly differentiated ZZ/ZW sex microchromosomes with a heterochromatic W chromosome in the Komodo dragon. Sex chromosomes have so far only been described in a few species of varanids including V. varius, the sister species to Komodo dragon, whose W chromosome is notably larger than that of the Komodo dragon. Accumulations of several microsatellite sequences in the W chromosome have recently been detected in 3 species of monitor lizards; however, these accumulations are absent from the W chromosome of the Komodo dragon. In conclusion, although varanids are rather conservative in karyotypes, their W chromosomes exhibit substantial variability at the sequence level, adding further evidence that degenerated sex chromosomes may represent the most dynamic genome part.
Keywords: Lizards; heterochromatin; ještěři; Microsatellite Repeats; Sex Chromosomes; Male; Animals; molekulární evoluce; karyotyp; pohlavní chromozomy; mužské pohlaví; ženské pohlaví; Evolution, Molecular; Female; Heterochromatin; zvířata; Karyotype; mikrosatelitní repetice